Screening and grading of brinjal (Solanum melongena) accessions for resistance to spotted beetle (Henosepilachna vigintioctopunctata) - RAJENDRAN, B; GOPALAN, M (The Indian Journal of Agricultural Sciences, 2013)
Brinjal or egg plant (Solanum melongena L.) is attacked by the spotted leaf beetle (HenosepilachnavigintioctoPunctata Fab : Coccinellidae : Coleoptera). Both adults and larvae feed on the leaves and under severeepidemic, the crop yield is highly reduced (Krishnamurti and Appana 1951). It is also polyphagus on hosts like potato(Solanum tuberosum L.), tomato (Lycopersicon esculentum Mill) and bittergourd (Momordica charantia L.) (Rajagopalanand Trivedi 1989). Since insecticide asage is highly disfavoured in egg plant, alternatively identifying resistance forspotted beetle was attempted earlier (Sambandam et al. 1972). Screening method involving in vitro method wasutilized by Natarajan (1971). The mean leaf-area fed by known number of beetles for specific period was taken as abasis for evaluating the entries earlier. In this method, the intensity of leaf -damage was alone taken as the criterion forgrading and the percentage incidence of damage under field conditions was not taken into account. The number ofleaves affected in a plant also contributed towards yield potential of the plant. Hence in the present method, both theincidence (percentage of leaves affected) under field conditions and intensity (leaf area damage/unit time) were assessedand damage index computed for grading of resistance.